PENGARUH VIRAL MARKETING DAN BRAND AWARENESS TERHADAP INTENSI PEMBELIAN - Arfandi, Mohammad Wilham; Arif, Moh. Erfan (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Internet use in Indonesia has increased due to Covid-19 which requires all activities outside the home to be carried out online. Thus, there is an opportunity for each product to be promoted through the internet, be it social media or online shopping. The purposes of this research are to examine the effect of viral marketing and brand awareness on purchase intention. The type of this study is descriptive research that explains the characteristic and nature of the research. The sampling technique uses non-probability sampling and purposive sampling. The research collected data from 128 respondents by conducting a survey through online questionnaire. The research sample consisted of respondents aged over 18 years and respondents who had subscribed and were viewers (non-subscribers). to RANS Entertainment YouTube channel. SEM-PLS testing were used to analyzed the data with SmartPLS. From the results of the hypotheses testing, it can be concluded that viral marketing has not significant effect on purchase intention. Brand awareness has significant effect on purchase intention. In this study, it can be said that the viral marketing variable is not able to attract purchase intentions for Kopi Gilus Mix products while the brand awareness variable is able to attract purchase intentions.